Autophagy in emerging and highly concerned severe zoonotic infectious diseases - Qi, Yubo; Wang, Lingjie; Wu, Shengping; Meng, Chi; Chu, Yuefeng; Yin, Yulong; Jiao, Hanwei (Frontiers in Immunology, 2026)
Autophagy is a conserved cellular process that mediates degradation of damaged organelles, misfolded proteins, and invading pathogens, playing critical roles in intracellular homeostasis and immune regulation. Given that over 70% of infectious diseases and 60% of emerging infectious diseases are zoonotic, posing a major threat to global health, this review aims to summarize the cellular and molecular mechanisms underlying the crosstalk between autophagy and key zoonotic pathogens. We comprehensively retrieved relevant research literature from the PubMed, Web of Science, and Scopus databases (with the retrieval deadline set as December 2025), using core keywords including autophagy, zoonoses, and pathogen-host interactions. The inclusion criteria were original studies and high-quality reviews focusing on molecular mechanisms or clinical translational potential. Finally, a total of 216 core literatures were included for comprehensive analysis. This review is a narrative overview with comprehensive coverage, aiming to systematically summarize the research progress of autophagy in zoonoses, rather than a systematic meta-analysis strictly adhering to the PRISMA guidelines. Key findings include (1): Autophagy can restrict the replication of zoonotic pathogens such as influenza virus and Brucella by mediating their degradation; (2) Some pathogens have evolved strategies to hijack or inhibit autophagy for survival; (3) Several autophagy-related molecules (e.g., ATG5, Beclin-1) have been identified as potential targets for zoonoses prevention and treatment. This review highlights the dual role of autophagy in zoonotic infections and its potential as a therapeutic target. However, further studies are needed to clarify species-specific differences in autophagy regulation and develop targeted interventions. These insights may provide new avenues for the prevention and treatment of severe zoonotic diseases.